Natural Gas Sales Optimization Strategy of PT XYZ in East Java - Tulus Sajiwo; Sumarwan, Ujang; Asnawi, Yudha Heryawan (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The condition of supply and demand for natural gas in East Java will experience dynamics, based on government work plans for Java gas pipeline, Tuban refinery and new gas field development. This research aims to analysis and simulate the gas market from 2021 to 2035 and develop gas marketing strategy to optimize PT XYZ's revenue. The Dynamic Model System method is used in scenario and market analysis, the AHP method is used for segmentation, targeting and positioning, while the Focus Group Discussion is used for the implementation strategy of optimizing revenue from gas sales. The results of the study show that during the period 2022 – 2025, the gas market in East Java experienced an excess of gas supply by 249 mmscfd, the second period in 2026-2030 the gas market was still a surplus of 53 mmscfd, but in 2030-2035 the gas market experienced a shortage of 260 mmscfd. PT XYZ's strategy is to prioritize the fertilizer sector, PGN industry and electricity through gas traders as the main buyers by using the main criteria for volume, utilization period and gas price as a reference in preparing scenarios and implementation strategies. The scenario is optimistic that the improve in gas production and maximize gas marketing will increase PT XYZ's revenue and position as the market leader in East Java. Keywords: AHP, gas marketing, natural gas, optimization, system dynamic model